Compreensão de estruturas com movimento A´ em crianças com Perturbações do Espectro do Autismo - Costa, Raquel; Lobo, Maria (Revista da Associação Portuguesa de Linguística, 2022)
This investigation aims to study the comprehension of A´movement (wh-questions and relatives) in L1 European Portuguese children with Autism Spectrum Disorder (ASD), since previous research on syntactic abilities in ASD remains inconclusive. 24 Portuguese speaking children with ASD (aged 5;6 to 13;11), including children with low and high non-verbal IQ, were compared to 35 typically developing (TD) children. The comprehension of subject, object and oblique wh-questions and subject, object and oblique relatives was assessed via a picture selection task. Overall, ASD children seem to have more difficulties than the control group with these structures, although there were only statiscally significant differences between the control group and the experimental group in younger children. No significant differences were found between ASD children with low and high IQ, with heterogeneous behavior in both groups. The results are in line with the ones we find in studies with this population conducted in other languages that suggest that ASD may be associated with general language delays and that there is a dissociation between non-verbal IQ and the comprehension of syntactic structures.